Introduction. Antarctic ecology: from genes to ecosystems. Part 2. Evolution, diversity and functional ecology. - Rogers, A; Murphy, E; Johnston, N; Clarke, A (2007)
The Antarctic biota has evolved over the last 100 million years in increasingly isolated and cold conditions. As a result, Antarctic species, from micro-organisms to vertebrates, have adapted to life at extremely low temperatures, including changes in the genome, physiology and ecological traits such as life history. Coupled with cycles of glaciation that have promoted speciation in the Antarctic, this has led to a unique biota in terms of biogeography, patterns of species distribution and endemism. Specialization in the Antarctic biota has led to trade-offs in many ecologically important functions and Antarctic species may have a limited capacity to adapt to present climate change. These include the direct effects of changes in environmental parameters and indirect effects of increased competition and predation resulting from altered life histories of Antarctic species and the impacts of invasive species. Ultimately, climate change may alter the responses of Antarctic ecosystems to harvesting from humans. The unique adaptations of Antarctic species mean that they provide unique models of molecular evolution in natural populations. The simplicity of Antarctic communities, especially from terrestrial systems, makes them ideal to investigate the ecological implications of climate change, which are difficult to identify in more complex systems.